The Effectiveness Test of Betel Leaf Ethanol Extract Cream (Piper Betle Linn) Toward Propionibacterium acnes Bacterial Growth - Krisyanella; Resva Meinisasti; Zamharira Muslim; Raden Sunita (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2020)
Background: One of skin diseases that is frequently taking attention among teenagers and young adults is acne or in medical term called acne vulgaris. Acne treatment can be treated by repairing follicular abnormalities, decreasing sebum production, decreasing the number of Propionibacterium acnes colonies and reducing inflammation of the skin. The bacterial population of Propionibacterium acnes can be reduced by giving an antibacterial substance such as erythromycin, clindamycin and benzoyl peroxide. In the treatment of acne we can get antibacterial originating from nature, one of which can be obtained in the secondary metabolism of plants. The extracts and essential oils of betel leaf contain antibacterial and antifungal activities. The effectiveness of the use of betel leaf ethanol extract (Piper betle Linn) in acne treatment can be improved by creating formulations in form of cream preparations. Formulations in cream preparations will affect the amount and speed of active substances that can be absorbed. Objectives: To determine the effectiveness of the ethanol extract cream of betel leaf (piper betle linn) cream in formulas with what percentage of active substance has the most-inhibitory effect on the growth of Propionibacterium acnes. Methods:The study used experimental research. Propionibacterium acnes samples were diluted in 0.9% physiological NaCl sterile and embedded in Nutrient Agar (NA) media. The media was inserted into an incubator at 37 Â° C for 24 hours. The test of antibacterial activity used the disk diffusion method. The antibacterial activity test results were statistically analyzed using the Statistical Product Services Solution (SPSS 17) program with a confidence level of 95% (Î± = 0.05). Results: The three creams containing betel leaf ethanol extracts at percentages of 5%, 10% and 15% for each had inhibitory zones: 9.8 mm, 15.85 mm, 17.35 mm. Conclusion: Cream that contains 15% active substance has the strongest inhibition.